Persepsi Masyarakat Terhadap Kinerja Pengawasan Dprd Kota Palembang Di Kecamatan Kemuning Dalam Menangani Isu Pelayanan Publik - Muhammad Alzena Akbar; R.A. Julia Pratiwi; Rina Pebriana (Journal of Innovative and Creativity, 2026)
This study aims to determine public perceptions of the oversight performance of the Palembang City Regional Representative Council (DPRD) in Kemuning District in addressing public service issues. The DPRD, as a regional legislative body, plays a strategic role in absorbing public aspirations, overseeing local government policies, and ensuring that public services meet citizen needs. However, in practice, various public complaints persist regarding transparency, responsiveness, and the follow-up of public aspirations. This study used a qualitative approach using in-depth interviews with residents of Kemuning District aged 17 and over. The data obtained were analyzed using thematic analysis techniques to identify patterns of meaning that emerged from the experiences and perspectives of informants. The analysis revealed several key themes shaping public perceptions: transparency of DPRD performance, level of public trust, effectiveness of recess as a means of gathering aspirations, oversight of public services and development projects, and handling of employment issues. The discussion of the research findings is linked to Agenda-Setting Theory to understand how frequently raised and discussed issues influence assessments of DPRD performance. Research findings indicate that low transparency and weak follow-up of aspirations have led some members of the public to hold negative perceptions of the DPRD's oversight performance. Therefore, increasing transparency, open communication, and strengthening the oversight function are crucial steps in building public trust and improving the quality of public services in Palembang City.